2013
DOI: 10.1007/s00425-013-2006-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the substrate recognition region in the Δ6-fatty acid and Δ8-sphingolipid desaturase by fusion mutagenesis

Abstract: Δ⁸-sphingolipid desaturase and Δ⁶-fatty acid desaturase share high protein sequence identity. Thus, it has been hypothesized that Δ⁶-fatty acid desaturase is derived from Δ⁸-sphingolipid desaturase; however, there is no direct proof. The substrate recognition regions of Δ⁶-fatty acid desaturase and Δ⁸-sphingolipid desaturase, which aid in understanding the evolution of these two enzymes, have not been reported. A blackcurrant Δ⁶-fatty acid desaturase and a Δ⁸-sphingolipid desaturase gene, RnD6C and RnD8A, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Mutagenesis studies have revealed that the second putative TMH, the regions adjacent to the conserved histidine motifs and the Cterminus affect the regioselectivity and the preferred substrate chain length of membrane desaturases. 10,11,25,26 However, although Δ6-desaturases have been identified that naturally prefer either ω3 or ω6fatty acids, 23,[27][28][29][30][31] detailed mutagenesis studies to modify ω3/ω6fatty acid preference have not been performed, to the best of our knowledge. Similarly, the evolution of ω3/ω6fatty acid specificity, including divergence between MpΔ6des and OtΔ6des, has not been investigated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Mutagenesis studies have revealed that the second putative TMH, the regions adjacent to the conserved histidine motifs and the Cterminus affect the regioselectivity and the preferred substrate chain length of membrane desaturases. 10,11,25,26 However, although Δ6-desaturases have been identified that naturally prefer either ω3 or ω6fatty acids, 23,[27][28][29][30][31] detailed mutagenesis studies to modify ω3/ω6fatty acid preference have not been performed, to the best of our knowledge. Similarly, the evolution of ω3/ω6fatty acid specificity, including divergence between MpΔ6des and OtΔ6des, has not been investigated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…DES specificity relies on intricate substrate features, including the acyl-chain position, length, unsaturation features, and the acyl-carrier nature (Heilmann et al ., 2004a; Li, D et al ., 2016). Domain swapping between DES of distinctive specificity, together with further amino acid mutation, could highlight the primary importance of His-Box and surrounding region for front-end desaturase activity and substrate specificity (Song et al ., 2014; Li, D et al ., 2016; Watanabe et al ., 2016). However, neither the exact molecular features underlying DES (regio)specificity nor the hierarchical importance of the substrate features are yet clearly identified.…”
Section: Discussionmentioning
confidence: 99%
“…Protein engineering has been applied to understand the structure-function relationship. For instance, domain swapping has been used to identify the regioselective sites of nematode ⌬ 12 and 3 desaturases ( 12 ), a region determining the substrate specifi city of Aspergillus nidulans ⌬ 12 and 3 desaturases ( 13 ), and a substrate recognition region of black currant ⌬ 6 fatty acid desaturase and ⌬ 8 sphingolipid desaturase ( 14 ). Site-directed mutagenesis based on amino acid sequence comparison has been used to identify amino acids participating in the substrate specifi city of Mucor rouxii D6d ( 15 ), Siganus canaliculatus ⌬ 4 and D5d/D6d ( 16 ), and marine copepod ⌬ 9 desaturase ( 17 ).…”
Section: Site-directed Mutagenesismentioning
confidence: 99%
“…The corresponding genes are positioned in a head-to-head confi guration on the rat genome, suggesting a paralogous relationship ( 11 ). Although their primary structures are highly homologous, they are in charge of mutually exclusive substrates: D6d catalyzes the conversion of linoleic acid (LA; 18:2 ⌬ 9,12) and ␣ -linolenic acid (18:3 ⌬ 9,12,15) into ␥ -linolenic acid (GLA; 18:3 ⌬ 6,9,12) and stearidonic acid (18:4 ⌬ 6,9,12,15), respectively, whereas D5d acts on dihomo-␥ -linolenic acid (DGLA; 20:3 ⌬ 8, 11,14) and eicosatetraenoic acid (20:4 ⌬ 8,11,14,17) to generate arachidonic acid (ARA; 20:4 ⌬ 5, 8,11,14) and eicosapentaenoic acid (20:5 ⌬ 5,8,11,14,17), respectively. To identify and evaluate the amino acid residues important for substrate selection of D6d, we performed additional analyses on the basis of the primary sequence of zebra fi sh bifunctional ⌬ 5/6 desaturase [zD5/6d ( 23 )] and the recently reported crystal structure of human stearoyl-CoA ( ⌬ 9) desaturase ( 24,25 ).…”
Section: Site-directed Mutagenesismentioning
confidence: 99%